The Issue of the Protection of Human Life, i.e.: The Necessity of Recognition of Love to the Human Being as the Basis of Respect to the Natural Environment - Biały, Stanisław (Studia Ecologiae et Bioethicae, 2007)
The point of departure for the reflections in this article was the premise that the ecological crisis is the result not only of the degradation of nature, but also comes from the destruction of that environment, which is the spirituality of modern man. the point is that the more and more intensive use of the biosphere causes many unfavorable chemical and biological changes in the natural environment, which not only have their source in the way of thought and acting of man, but also have their effects on these. Because of this, the author comes to the conclusions that among the fundamental tasks that are before the world of today, one must also include the equiping of man with an ecological knowledge (that is: with a determined set of information connected in a causal-consecutive system on the subject of the functioning of the natural environment and the dependences between it and civilization), but above all: with a system of values and their normative equivalents. Only in such a manner can people be instilled with an adequate attitude, understood as a developed feeling of a link with the world of nature and its parts. We speak here of the readiness for its defense, manifested in concrete actions. Thus , an essential role of such a scientific discipline as environmental ethics shall be giving people the proper catalog of values and norms, which could properly form their motivations, attitudes and behavior as regards the natural environment, which at the end we call the relation of man to himself.